An Analysis of Metaphorical Expressions in Postcolonial Novel: A House for Mr. Biswas by V.S Naipaul - Indah Rahmawati; Dwijani Ratnadewi (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2015)
This research was conducted to investigate the types of metaphor and analyze the illocutionary meaning of the metaphors in the dialogues in the novel of V.S. Naipaul‘s A House for Mr. Biswas. This research aimed to get clear descriptions of the types of metaphor found in the novel, the implied meaning of the metaphors, the author‘s motive and the possible connection with British colonialism and slavery. Descriptive qualitative approach was used in conducting the research. Meanwhile, pragmatics was applied as the frame of the study. The data used in this research were the metaphors found in the dialogues. The research was conducted by classifying the types of metaphor, describing the context of the utterance, interpreting the illocutionary meaning, and analyzing the metaphors using postcolonial perspective. It was found twenty one metaphors, which were categorized into six types they were: dead, ordinary, cliché, standard, image, and original metaphor. It was also found that some metaphors in the dialogues represented the psychological condition of the postcolonial people, they were oppression, alienation and depression. The research also presented at least three evidences which led to the conclusion that the story was a symbolic representation of British colonialism and slavery.